Mobile media, gender, and power in rural India - Tenhunen, Sirpa (Human Technology, 2019)
This article traces the diffuse connections between mobility and power by exploring how mobile phone use contributed to gendered power relations in rural India. It is based on ethnographic fieldwork on the use of mobile phones, conducted periodically between 2005 and 2013 in the village of Janta in West Bengal, India, and compared to earlier fieldwork in Janta, before the village had any phone system. Analysis of the increased mobility reveals how mobile phone use emerges within interconnected, changing fields of power. The political sphere earlier perceived as predominantly local was replaced by translocal political practices characterized by increasing mobility. Although new political practices eroded women’s political participation in the village, mobile phone use made possible new forms of agency for women. The article contributes to the understanding of the unanticipated ways mobility and new media contribute to power and politics.